PENGARUH BYSTANDER EFFECT, KESESUAIAN, KOMPENSASI, DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN.(FRAUD) AKUNTANSI PADA LEMBAGA.PERKREDITAN DESA (LPD) SE-KECAMATAN PENEBEL - Ni Wayan Redini Nariya Wati; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2021)
Tendency of Fraud Accounting is a fraudulent act committed by a person or group for the sake of personal and group gain at the expense of many other parties. This study aims to determine the effect of the bystander effect, the suitability of compensation and individual morality on the tendency of accounting fraud at Lembaga Perkreditan Desa (LPD) in Penebel district. The population in this study were all employees of the LPD’s in Penebel District, the respondents used were 104 people consisting of the Head of the LPD and the LPD Treasurer. The method of.determining the sample using purposive sampling technique. From the results of this study, the bystander effect has a positive effect and significant on the tendency of accounting fraud, while the suitability of compensation and individual morality does.not have a significant effect on the tendency of accounting.fraud.